THE FACTORS AFFECTING THE INCOME OF SOYBEAN FARMING IN KULON PROGO REGENCY - Fitry Purnamasari; Sri Hardianti Rosadi; Hasnah Hasnah (Agribusiness Journal, 2021)
This study aims to determine the factors that affect the income of soybean farming. This research was conducted in Kulon Progo Regency with the number of respondents as many as 50 farmers. This study uses the Cobb-Douglas profit function with the technique Unit Output Price or UOP of Cobb Douglas Profit Function ( UOP-CDPF). This research has been declared valid, reliable, the data is normally distributed, free from multicollinearity and heteroscedasticity problems, so that multiple linear regression analysis can be carried out. The results showed that the R2 value was 36.7%, so the variation in soybean income could be explained by the eight independent variables and the rest explained by variables outside the model. The results of the F test show that the independent variables of seed prices, NPK fertilizer prices, manure prices, Gandasil fertilizer prices, pesticide prices, labor wages, land area and the rate of adoption of GAP (Good Agriculture Practices) together have an effect on soybean income. The t test results show that the increase in soybean farming income is influenced by the increase in labor wages, land area and the level of GAP adoption. Keywords : Cobb-Dauglas, Profit Function, , Soybean, Income